Proteomics and its Related Biological Activity of Jatropha tanjorensis Ellis & Saroja: An Ethnomedicinal Plant - Arun, K.P.; Balaji, P.; Sivashankari, P.R.; David Raj, C.; Brindha, P. (Asian Journal of Chemistry, 2014)
Traditionally Jatropha tanjorensis is being used as an alternative medicine and the phytochemical investigation of this plant has proved that the leaves contain antioxidant, anti-hyperglycaemic and antiinflammatory bio molecules. The crude protein extract was analyzed by non-reducing native-PAGE, which showed three prominent protein bands with molecular weight of about 78.6, 67.8 and 43.3 KDa. Further, 2D studies and mass spectrometric (MS) analysis were done separately. Protein separations were examined using pH 3-10 non-linear IEF strip. Totally 89 protein spots were detected differing in their pI values, suggesting a possible difference in their electrostatic charge. In regard to mass spectrometric analysis coupled with in-gel digestions were performed for 5 major protein spots using trypsin and were identified through peptide mass fingerprint of selected peptides in UHPLC-ESI-Quad-TOF and MALDI-TOF mass spectrometer. Proteomic approach lead to the identification of major proteins from J. tanjorensis. Among various proteins, redox enzymes and DNA binding proteins were found to be most abundantly extracted proteins. These classes of proteins are known for their antioxidant, antimicrobial and anticancer activities and hence the extracted proteins were evaluated for their biological activities with a view to develop a novel therapeutic agent. The proteins extract revealed potent antioxidant and antimicrobial activities, when compared to standards. It showed IC50 value as 173 μg/mL for DPPH scavenging, LPO inhibition (226.2 μg/mL) and hydroxyl ion reducing assays (269.5 μg/mL). In antimicrobial studies it was effective against both gram positive and negative bacteria’s such as S. aureus MTCC 96, S. aureus MTCC EI, P. aeruginosa MTCC 741, P. aeruginosa MTCC EI, B. subtilis MTCC 441 and E. coli MTCC 723 with MIC values ranging from 7.8-15.6 μg/mL which are comparable to MIC values of standard antibiotics. Jatropha tanjorensis protein extract has also shown potent cytotoxicity against Ehrlich ascites carcinoma (EAC) with an IC50 of 49.9 μg/mL. Present study scientifically proves the traditional usage of Jatropha tanjorensis as a health tonic and for the management of microbial infections.